Interpreting Article 22(2) of the 1945 Constitution of the Republic of Indonesia Post Constitutional Court Decision 54/PUU-XXI/2023 - Riqiey, Baharuddin; Huda, Muhammad Ahsanul (Universitas Negeri Semarang, 2024)
The aim of this research is to elucidate the interpretation of Article 22, paragraph (2) of the 1945 Constitution of the Republic of Indonesia, particularly focusing on the phrases